Nipple candidiasis and painful lactation: an updated overview - Plachouri, Kerasia-Maria; Mulita, Francesk; Oikonomou, Chrysa; Papadopoulou, Margarita; Akrida, Ioanna; Vryzaki, Eleftheria; Verras, Georgios-Ioannis; Georgiou, Sophia (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
Nipple pain and discomfort during or after breastfeeding remains one of the most common reasons for premature cessation of lactation among the affected women. The belief that yeasts, and especially Candida spp., are responsible for such symptoms is highly supported by many physicians, midwives, or lactation specialists, but is also viewed with scepticism by other health care providers. The aim of this paper is to provide an updated report of the evidence against, as well as in favour of, the “Candida hypothesis”. Several studies have documented that lactating women with symptoms such as nipple soreness, with or without radiating breast pain, are more likely to test positive for Candida spp. than non-symptomatic women. However, its role as an undisputable aetiopathogenic factor for infection in these cases cannot always be established. Physicians should evaluate thoroughly such patients, because early and correct recognition of the underlying problem can prevent phenomena of early weaning.